2016
DOI: 10.1002/cne.24079
|View full text |Cite
|
Sign up to set email alerts
|

Computation of a high‐resolution MRI 3D stereotaxic atlas of the sheep brain

Abstract: The sheep model was first used in the fields of animal reproduction and veterinary sciences and then was utilized in fundamental and preclinical studies. For more than a decade, magnetic resonance (MR) studies performed on this model have been increasingly reported, especially in the field of neuroscience. To contribute to MR translational neuroscience research, a brain template and an atlas are necessary. We have recently generated the first complete T1-weighted (T1W) and T2W MR population average images (or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 71 publications
0
37
0
Order By: Relevance
“…Overall, ventricular enlargement was more pronounced in CLN5 − / − animals than in CLN6 − / − animals, which may indicate a differing pattern of brain atrophy in the different types of ovine NCL. In recent past, a high‐resolution sheep brain MRI atlas has been established based on the brains of 18 sheep and it showed that the mean volume of the lateral and third ventricles combined was approximately 4.9 ml (Ella & Keller, 2015; Ella, Delgadillo, Chemineau, & Keller, 2017). The discrepancy between these measures and the measures recorded in the present study is likely consequent to differences in the measurement techniques and issues with the spatial resolution of the CT scanner used, and the present measures reflect the ventricular volumes sufficiently to compare affected and normal sheep within the same trial.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, ventricular enlargement was more pronounced in CLN5 − / − animals than in CLN6 − / − animals, which may indicate a differing pattern of brain atrophy in the different types of ovine NCL. In recent past, a high‐resolution sheep brain MRI atlas has been established based on the brains of 18 sheep and it showed that the mean volume of the lateral and third ventricles combined was approximately 4.9 ml (Ella & Keller, 2015; Ella, Delgadillo, Chemineau, & Keller, 2017). The discrepancy between these measures and the measures recorded in the present study is likely consequent to differences in the measurement techniques and issues with the spatial resolution of the CT scanner used, and the present measures reflect the ventricular volumes sufficiently to compare affected and normal sheep within the same trial.…”
Section: Discussionmentioning
confidence: 99%
“…Manual segmentation of the cortical structures was based upon published MRI sheep brain atlases [24,25]. The hippocampus was defined based upon the Michigan State sheep brain atlas [26] and was determined by a detailed examination in each of the orthogonal imaging planes.…”
Section: Segmentation Of the Cortical Structures And Hippocampusmentioning
confidence: 99%
“…Briefly, we defined the frontal cortex by the areas defined as 1, 4, 13, 14, 15, 19, and 22 in Ella et al 2017 [24]. This region was chosen because the tissue boundaries were readily discernible and it was not significantly impacted by scanning artefacts due to undissolved gas (in contrast to the lateral ventricles).…”
Section: Segmentation Of the Cortical Structures And Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic and research interpretation of such techniques requires the knowledge and unambiguous identification of areas and regions; one of the most complex CNS structures being the brain. Brain atlases are therefore fundamental tools for several clinical and research purposes [15]. One essential aspect of such research activities is the need to compare, and thus identify, brain structures and areas across different modalities (from macroscopic modalities to histological studies).…”
Section: Introductionmentioning
confidence: 99%